Generation of Vascular Endothelial Cells and Hematopoietic Cells by Blastocyst Complementation - Sanae Hamanaka; Ayumi Umino; Hideyuki Sato; Tomonari Hayama; Ayaka Yanagida; Naoaki Mizuno; Toshihiro Kobayashi; Mariko Kasai; Fabian Patrik Suchy; Satoshi Yamazaki; Hideki Masaki; Tomoyuki Yamaguchi; et al. (Stem Cell Reports, 2018)
Summary: In the case of organ transplantation accompanied by vascular anastomosis, major histocompatibility complex mismatched vascular endothelial cells become a target for graft rejection. Production of a rejection-free, transplantable organ, therefore, requires simultaneous generation of vascular endothelial cells within the organ. To generate pluripotent stem cell (PSC)-derived vascular endothelial cells, we performed blastocyst complementation with a vascular endothelial growth factor receptor-2 homozygous mutant blastocyst. This mutation is embryonic lethal at embryonic (E) day 8.5–9.5 due to an early defect in endothelial and hematopoietic cells. The Flk-1 homozygous knockout chimeric mice survived to adulthood for over 1 year without any abnormality, and all vascular endothelial cells and hematopoietic cells were derived from the injected PSCs. This approach could be used in conjunction with other gene knockouts which induce organ deficiency to produce a rejection-free, transplantable organ in which all the organ's cells and vasculature are PSC derived. : In this article, Yamaguchi and colleagues generated vascular endothelial cells and hematopoietic cells from pluripotent stem cells in vivo by blastocyst complementation technique. This approach could be used to produce a rejection-free, transplantable organ in which all the organ's cells and vasculature are pluripotent stem cell derived. Keywords: tissue regeneration, vascular endothelial cells, hematopoietic cells, blastocyst complementation, pluripotent stem cells